Transfer length prediction in pre-tensioned concrete beams under corrosive cracking. (April 2021) - Dai, Lizhao; Chen, Hong; Wang, Lei; Ma, Yafei; Zhang, Jianren
Abstract: An analytical model is proposed to predict the transfer length in pre-tensioned concrete (PC) beams under corrosive cracking. The coupling effects of Hoyer effect and corrosion-induced cracking are incorporated in the proposed model. An experimental study is employed to assess the transfer length in PC beams under corrosive cracking. The influence of strand corrosion on the effective prestress and transfer length is investigated by the four-point bending test. Experimental results are employed to validate the accuracy of the analytical model. Results show that the transfer length depends on the corrosion degrees and corrosion positions. The transfer length increases by 24.3% once the corrosion loss of strand reaches 35%. The transfer length with the corrosion loss of 35% will extend 8.6% when the corrosion position moves from the mid-span to the beam end. The elastic modulus of concrete and the Poisson's ratio of strand can affect the transfer length in PC beams under corrosive cracking. The transfer length under corrosive cracking will increase with the increase of elastic modulus of concrete and Poisson's ratio of strand, and Poisson's ratio of strand has a significant effect on the transfer length as compared to the elastic modulus of concrete.